Child Support, Father–Child Contact, and Preteens’ Involvement with Nonresidential Fathers: Racial/Ethnic Differences - Hofferth, Sandra L. (2010)
This study examined how child support, frequency of contact with children, and the relationship between nonresidential parents influenced preteens’ reports of the involvement of fathers and mothers in their life. Data are from the National Longitudinal Survey of Youth 1979 (NLSY79) that has followed the children of NLSY mothers from birth into their twenties. Results showed that increases in child support and in contact with the child over time after separation are linked to a better coparental relationship when children are age 11 or 12. This better relationship between parents is, in turn, associated with greater involvement of both mothers and nonresidential fathers with their children.